O discurso sobre a ciência no cronotopo pandêmico: uma análise dialógica - Weisshaar, Giliandra Aparecida da Cruz (2023)
In the last two years we have experienced the space-time of the pandemic, the pandemic chronotope, and in this chronotope we know that one of the main discourses, constantly thematized in dialogues was the discourse on science. This speech received great attention from the public sphere, was incessantly carried out, disseminated and shared in digital media. In view of this, the present research had the general objective of analyzing the discourses that emerged about science in the pandemic chronotope in digital media. Likewise, the specific objectives of this research are the following: a) To analyze the evaluative character of these statements about the ideological sphere of science, mainly, the question of the valuation of this discourse. b) Investigate and analyze how these discourses are also conflicting and contradictory since they are produced by subjects from different ideological positions. c) Investigate how the subjects of the pandemic chronotope are evidenced by these discursive productions. For the development of the research, we place it in the theoretical field of Dialogical Discourse Analysis (DDA), based on the writings of the Bakhtin Circle. Thus, we weave the research based on the precepts of ADD based on Acosta Pereira (2020a; 2020b), Brait (2014;2020), Paula (2013) and Rohling (2014; 2020) and on the theoretical assumptions of the Bakhtin Circle: BAKHTIN , (1997); BAKHTIN (2003); BAKHTIN (2002;2010) [1963]; BAKHTIN, 2018 [1975]; VOLOCHÍNOV, 2018 [1929]; VOLOSHINOV, (2013). In this theoretical framework, the main concepts addressed are discourse and statement, ideology and valuation, and chronotope. For the approach on displacements of conceptions about science, theorists Boaventura de Souza Santos (1978,1989, 2008) and Mikhail Bakhtin (2017) [1975] are approached. The data obtained for the analysis were collected from Twitter and Instagram digital media. With the data relation, it was observed the emergence of discursive regularities that highlight different positions of power over the discourse of science. The regularities are the contrasts between the discourse of science and the discourse of post-truth, the hierarchy between scientific and non-scientific subjects and also the clash between the different scientific spheres. From these regularities, the positions of different subjects and the dialogical clashes fought in the media in this pandemic chronotope on the discourse of science are observed. Finally, we conclude this research by noting that the discourse about science was extremely tense in this pandemic chronotope, several positions of different subjects expressed a dispute of voices, of meanings, about the discourse of science at that time, and in this way we reiterate the field of discourse as a space for uninterrupted clashes and tensioning of meanings.